Planning of Car Parking Spaces in Residential Areas of Tashkent City - Abbos O’g’li, Axmedov Shaxobiddinxon (Journal of Innovation in Education and Social Research, 2024)
The rapidly increasing number of motor vehicles in our country is causing a number of problems. Firstly, traffic jams occur on the roads and it becomes difficult to move, and secondly, maintenance of cars is becoming a serious problem. Due to the lack of special parking lots in settlements, neighborhoods, residential areas, including markets, offices, and other facilities, citizens illegally park their cars on sidewalks, entrances and exits of apartment buildings.